San Francisco City CarShare: Longer-term travel-demand and car ownership impacts - Robert Cervero; Aaron Golub; Brendan Nee (University of California, Institute of Urban and Regional Development (IURD), 2006)
This report examines the longer term impacts of the City CarShare program on travel demand and car ownership. It complements the previous analyses that focused on short and intermediate-term impacts. It gives particular focus to the question of whether the travel reduction evidence uncovered two years into the City CarShare program were sustained or gained momentum four years after the programs inception, or perhaps were short-lived and reversed course. As in the earlier studies, a matched pair comparison of travel patterns between members and a statistical control group of non-members is used. Factors that explain carshare members travel choices and car-shedding behavior are also modeled. The interested reader is referred to earlier reports for background on the City CarShare program, discussions of survey instruments and approaches, and details on the research methodology.
Keywords: 330